Theoretical and Experimental Study on the Antisliding Performance of Casting Steel Cable Clamps - Yangjie Ruan; Bin Luo; Mingmin Ding; Lifan Huang; Zhengxing Guo (Advances in Civil Engineering)
For large-span cable structures, a cable clamp is a key joint that connects adjacent structural components. In general, the antisliding performance of cable clamps determines their resistance capacity, and the antisliding force is generated by the clamping force induced by the high-strength bolts and the contact surfaces between the cable and the clamp. Since the existing methods are not sufficiently comprehensive for use to predict the precise bolt preload, a theoretical model developed by considering transversely isotropic material and the generalized Hook’s law is presented to predict the attenuation values of the bolt clamping force and the corresponding parameters. Then, to meet the requirements of Eurocode 3, a new laboratory test is performed to reveal the antisliding mechanism of cable clamps, considering the effects of long-term creep and cable tension. According to the results of the data collected by real-time monitoring, the actual ultimate antisliding force of the clamp and the comprehensive friction coefficient are determined. Finally, a comparative study between the theoretical results and the experimental results is conducted. The proposed theoretical model can predict the actual attenuation of the bolt clamping force after cable tension. The results show that the stiffness of the clamp plate should be minimized when designing the clamp to reduce the loss of the bolt preload.